The Non‐Classical Crystallization Mechanism of a Composite Biogenic Guanine Crystal. Issue 31 (26th June 2022) - Wagner, Avital; Ezersky, Vladimir; Maria, Raquel; Upcher, Alexander; Lemcoff, Tali; Aflalo, Eliahu D.; Lubin, Yael; Palmer, Benjamin A.
Abstract: Spectacular colors and visual phenomena in animals are produced by light interference from highly reflective guanine crystals. Little is known about how organisms regulate crystal morphology to tune the optics of these systems. By following guanine crystal formation in developing spiders, a crystallization mechanism is elucidated. Guanine crystallization is a "non‐classical, " multistep process involving a progressive ordering of states. Crystallization begins with nucleation of partially ordered nanogranules from a disordered precursor phase. Growth proceeds by orientated attachment of the nanogranules into platelets which coalesce into single crystals, via progressive relaxation of structural defects. Despite their prismatic morphology, the platelet texture is retained in the final crystals, which are composites of crystal lamellae and interlamellar sheets. Interactions between the macromolecular sheets and the planar face of guanine appear to direct nucleation, favoring platelet formation. These findings provide insights on how organisms control the morphology and optical properties of molecular crystals. Abstract : By following crystal formation in embryonic spiders, a long‐sought crystallization mechanism for biogenic guanine is revealed. Guanine nucleates from a disordered precursor phase. The crystals grow by the orientated attachment of partially ordered nanogranules into platelets, which coalesce into single crystals, via gradual relaxation of structural defects. The mature guanine is a composite of crystal lamellae intercalated by macromolecular sheets.